2015
DOI: 10.1590/1414-431x20154429
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise prevents motor disorders and striatal oxidative imbalance after cerebral ischemia-reperfusion

Abstract: Stroke is the third most common cause of death worldwide, and most stroke survivors present some functional impairment. We assessed the striatal oxidative balance and motor alterations resulting from stroke in a rat model to investigate the neuroprotective role of physical exercise. Forty male Wistar rats were assigned to 4 groups: a) control, b) ischemia, c) physical exercise, and d) physical exercise and ischemia. Physical exercise was conducted using a treadmill for 8 weeks. Ischemia-reperfusion surgery inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…However, 25 studies were excluded because the majority did not present oxidative stress analysis in their methodology or did not present studies related to rehabilitation exercise . Five articles [1,[38][39][40][41] were included in their summaries the keywords. However, during the reading of the full text, only the paper of Ciancarelli et al [40] met the inclusion criteria of our research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 25 studies were excluded because the majority did not present oxidative stress analysis in their methodology or did not present studies related to rehabilitation exercise . Five articles [1,[38][39][40][41] were included in their summaries the keywords. However, during the reading of the full text, only the paper of Ciancarelli et al [40] met the inclusion criteria of our research.…”
Section: Resultsmentioning
confidence: 99%
“…Stroke is the most common type since 85% to 90% of people were diagnosed with ischemic stroke [1]. Pathophysiology of stroke, there is a change in the encephalic circulation, leading to limitations in the performance of body structure and function [2].…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise is a noninvasive and easy alternative to influence the cognitive functions. Previous studies of our laboratory demonstrated that chronic aerobic exercise minimizes mnemonic deficits in animal models of neurodegenerative diseases [24, 36, 47], which have been related to antioxidant and anti-inflammatory exercise effects [23, 27], besides the exercise influence on neuroplasticity [28]. However, acute aerobic exercise is still studied little as a neuroprotective strategy [48].…”
Section: Discussionmentioning
confidence: 99%
“…One is the physical exercise. Chronic aerobic exercise effects on cognition are widely studied [23, 24], and researches demonstrated that exercise improves behavioral, mental health [25, 26] and biochemical parameters [23, 27, 28]. Despite other mechanisms involved on the aerobic exercise effects, it acts by exciting the central nervous system through positive regulation of catecholamines, including epinephrine (E), NE, and DA [2932].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies that propose the administration of antioxidant agents have been widely tested to prevent or treat hemorrhagic stroke [ 30 , 31 ]. Previous studies have already demonstrated the neuroprotective effects of green tea on balance in ICH [ 12 ] and brain ischemia-reperfusion models [ 18 , 32 ]. It is known that ICH injury mechanisms are related to increased free radical production and consequent oxidative stress [ 9 , 28 ].…”
Section: Discussionmentioning
confidence: 99%